The pragmatics of luxury - Diez-Arroyo, Marisa (Círculo de Lingüística Aplicada a la Comunicación, 2020)
This paper investigates the lexical items used in online automobile advertising to characterize the motorcar as a luxury product. The main questions examined are, firstly, how certain words are interpreted as denoting luxury concepts by potential readers, and, secondly, whether luxury and non-luxury marques differ in the use of these units. The issues here are addressed from a double theoretical framework: a theory of luxury, which allows for the identification and classification of the vocabulary of luxury, and Relevance Theory, a pragmatic model which explains how words are subject to pragmatic modulation during interpretation, leading to the construction of ad hoc concepts.